2014
DOI: 10.1021/am404876p
|View full text |Cite
|
Sign up to set email alerts
|

All-Solution-Processed Inverted Quantum-Dot Light-Emitting Diodes

Abstract: Quantum dots are a promising new candidate for the emissive material in light-emitting devices for display applications. The fabrication of such devices by solution processing allows considerable cost reduction and is therefore very attractive for industrial manufacturers. We report all solution-processed colloidal quantum-dot light-emitting diodes (QLEDs) with an inverted structure. The red, green, and blue devices showed maximum luminances of 12 510, 32 370, and 249 cd/m(2) and turn-on voltages of 2.8, 3.6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 24 publications
(35 reference statements)
0
72
0
Order By: Relevance
“…Assuredly, the current efficiency of our QD-LEDs is relatively much low in comparison with the recent works on QD-LEDs fabricated by vacuum evaporation technique. The typical current efficiency of QD-LEDs prepared by all-solution process (with nitrogen ambient in glove box) [36][37][38], combined solution-vacuum process [39], and transfer-printing method [26] is in the range of 0.3-5 cd A À1 . It is noted that our QD-LEDs were prepared by solution process in ambient air.…”
Section: Resultsmentioning
confidence: 99%
“…Assuredly, the current efficiency of our QD-LEDs is relatively much low in comparison with the recent works on QD-LEDs fabricated by vacuum evaporation technique. The typical current efficiency of QD-LEDs prepared by all-solution process (with nitrogen ambient in glove box) [36][37][38], combined solution-vacuum process [39], and transfer-printing method [26] is in the range of 0.3-5 cd A À1 . It is noted that our QD-LEDs were prepared by solution process in ambient air.…”
Section: Resultsmentioning
confidence: 99%
“…Further attempts are aimed to optimize charge injection, to transport, to improve stability of material and to control chemical and physical phenomena at the interface. Also, an all solution-processed QDLED with an inverted structure is investigated by Castan and his coworkers [45]. They demonstrated that the optimized amount of PTE in the PEDOT:PSS can balance the charge in the device.…”
Section: A Brief Review Of Quantum Dot-based Light Emitting Diodes (Qmentioning
confidence: 99%
“…Recent advances in QD sciences have led to nearly 100% quantum efficiency [13][14][15][16][17][18][19], while downconversion occurs only when the excitation light hits QD particles. The probability of hitting a QD particle depends on two factors: the QD particle density and the blue light path length.…”
Section: Qd Diffuser Filmmentioning
confidence: 99%